2002
DOI: 10.1007/s00251-002-0472-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of expressed DQA and DQB genes in the California sea lion ( Zalophus californianus )

Abstract: To date, there are no published MHC sequences from the California sea lion (Zalophus califomianus), a thriving species that, by feeding high on the marine food web, could be a sentinel for disturbances in marine and coastal ecosystems. In this study, degenerate primers and RACE technology were used to amplify near-fiiUThis study was supported by grants from the Office of Naval Resources (ONR), the Marine Community Foundation, the Fogarty International Center and the US National Science Foundation (#DEB-0094919… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…The nucleotide sequence of the Urth-DQB coding region (to the stop codon: 798 bp) had a similarity with the California sea lion DQB (94%), dog DQB (90%) and human DQB (87%). Bowen et al (2002) reported that the California sea lion DQB amino acid sequences contained DQ-specific motifs of 3 amino acids in the exon 3 region. These motifs are especially useful for distinguishing the DQB from DRB sequences in several species of mammal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleotide sequence of the Urth-DQB coding region (to the stop codon: 798 bp) had a similarity with the California sea lion DQB (94%), dog DQB (90%) and human DQB (87%). Bowen et al (2002) reported that the California sea lion DQB amino acid sequences contained DQ-specific motifs of 3 amino acids in the exon 3 region. These motifs are especially useful for distinguishing the DQB from DRB sequences in several species of mammal.…”
Section: Resultsmentioning
confidence: 99%
“…1. Nucleotide sequences of the near full-length DQB cDNA (Urth-DQB) and DQB exon 2 region (Urth-DQB*a to Urth-DQB*e) of the Asiatic black bear (this study), California sea lion (Bowen et al, 2002) and the dog DQB sequences (Wagner, unpublished;Debenham et al, 2005). Dots indicate identity with the nucleotides of Urth-DQB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exactly how much MHC diversity is required to ensure long-term population viability remains a fundamental question in conservation genetics. A lack of variation at the MHC may increase the susceptibility of an isolated population to infectious disease epidemics, with potentially catastrophic consequences (Bowen et al, 2002). For example, a link between MHC diversity and an effective response to both pathogenic and toxicogenic challenges was proposed (Acevedo-Whitehouse et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The most diverse and extensively studied MHC genes are the DQB and DRB genes. Diversity of DQB or DRB genes has been characterized in many mammalian species such as primates (Bontrop et al, 1999), bank vole (Axtner & Sommer, 2004), domestic mammals (Schook & Lamont, 1996, Yuhki & O'Brien, 1997, Mikko et al, 1999, Wagner et al, 1999, and marine mammals (Murray et al, 1999, Bowen et al, 2002, 2004, Baker et al, 2006, Hayashi et al, 2006, Xu et al, 2007. After these studies on non-model free-ranging species were carried out, intriguing questions were raised about whether and how selection operates on the MHC of natural populations characterized by distinct pathogens and demographic and environmental conditions (Bernatchez & Landry, 2003;Sommer, 2005).…”
Section: Introductionmentioning
confidence: 99%